Reduction of Mutual Coupling Between Two Circularly Polarized Magneto-Electric Dipole Antennas Using Metasurface Wall Polarization Converter for 5G Application - Mohammadhossein Ashouri; Saeed Fakhte (Majlesi Journal of Electrical Engineering)
The mutual coupling issue between two Right Hand Circularly Polarized (RHCP) Magneto-electric (ME) dipole antennas is addressed in this study. To mitigate this issue, a Metasurface Polarization-Rotator (MPR) Wall is employed, resulting in effective minimization of the coupling effects. The innovative antenna design, with high gain, shows promise for 5G applications. It consists of two electric dipole plates with triangular corners positioned at the top, along with two plates acting as magnetic dipoles perpendicular to the ground plane. Additionally, the presence of four plates on the outer periphery of the antenna contributes to the improvement of the circular polarization (CP) performance of the antenna. The feeding structure is configured in a V-shape. Integration of the metasurface polarization-rotator led to a significant reduction in mutual coupling. On average, the mutual coupling is decreased by more than -20.5 dB, reaching impressive values of -45 dB at 2 GHz, -55 dB at 3.1 GHz, and -40 dB at 3.7 GHz when the MPR wall is placed between the ME antennas. The antenna demonstrates promising performance in terms of impedance bandwidth, with a remarkable value of 61.4% for |S11| < [-10dB]. Furthermore, the axial ratio bandwidth for AR < [3 dB] is 63.36%, representing an 11% increase compared to the configuration without the MPR Wall. The maximum right-hand circular polarization gain achieved by the antenna is 9.91 dB at a frequency of 3 GHz. Additionally, the maximum front-to-back ratio (FBR) is 37.6 dB at a frequency of 2.5 GHz. By comparing and analyzing the simulation results for the scenarios with and without the MPR Wall, it becomes evident that the MPR Wall does not significantly affect the parameters of gain, front-to-back ratio, and impedance bandwidth.